SPEECH DISFLUENCY ANALYSIS ON ANXIETY SUFFERER REPRESENTED BY ZAYN MALIK: A PSYCHOLINGUISTIC APPROACH - Sukma Sukriana; Jufrizal Jufrizal; Delvi Wahyuni (English Language and Literature, 2018)
This research aimed to analyze the development of speech disfluency of Zayn Malik, ex-One Direction member, regarding his anxiety disorder issue since 2015 – 2017. The types of this research was descriptive qualitative through longitudinal analysis. Data for this research were 281 utterances from trancriptions of Zayn Malik’s speech based on ten videos taken from Youtube since 2015 until 2017. The result showed that there were 1369 types of speech disfluency. Silent pause and filled pause gave huge contribution to disrupt Zayn Malik’s speech. The most common types and the highest types of speech disfluency produced by Zayn Malik was filled pause that was 627 types or 72%. Surprisingly, Zayn Malik developed more silent pause than filled pause since the last of 2016 until the middle of 2017, and he no longer produced types of stuttering like prolongation or block since the middle of 2016. It proved that Zayn Malik is indeed a non-stuttered speaker. In relation to anxiety and speech disfluency, Zayn Malik were more anxious to speak in front of many audiences or with men interviewers because his speech disfluency increased; while it decreased when he talked to woman interviewer or a machine by seeing the result that he produced more silent pause during the interview. Hence, the best way to overcome stuttering for anxiety sufferer is by producing more silent pause during speech in order to create a good speaking performance.